The effect of career development and work motivation on employee job satisfaction at PT. SOURCE OF ALFARIA TRIJAYA, JAMBI CITY - kurniawan, Doni; Anwar Us, Kasful (Transpublika Publisher, 2021)
AbstractThis study aims to explain whether the variables of career development and motivationwork has a significant effect on employee job satisfaction at PT. SourceAlfaria Trijaya and knowing which variable is more dominant between the two.From the results of the data analyzed by using qualitative methods and quantitative methods,found results that show that together or simultaneously, the two factors thatIn this study, it has a positive effect on the independent variable, namely job satisfaction.employee with the result Y= ,???????????? + ,???????????? + , + . Then when in reviewFrom the results of the coefficient of determination, it is found that the magnitude of the contribution of the two variables isThis impact on performance satisfaction reached 59.9% and the rest was influenced by other factors, whichThus, it is concluded that the studied variable has an effect on job satisfactionemployees.